Small noncoding RNAs in FSHD2 muscle cells reveal both DUX4- and SMCHD1-specific signatures. (8th May 2018) - Lim, Jong-Won; Wong, Chao-Jen; Yao, Zizhen; Tawil, Rabi; van der Maarel, Silvère M; Miller, Daniel G; Tapscott, Stephen J; Filippova, Galina N
Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is caused by insufficient epigenetic repression of D4Z4 macrosatellite repeat where DUX4, an FSHD causing gene is embedded. There are two forms of FSHD, FSHD1 with contraction of D4Z4 repeat and FSHD2 with chromatin compaction defects mostly due to SMCHD1 mutation. Previous reports showed DUX4-induced gene expression changes as well as changes in microRNA expression in FSHD muscle cells. However, a genome wide analysis of small noncoding RNAs that might be regulated by DUX4 or by mutations in SMCHD1 has not been reported yet. Here, we identified several types of small noncoding RNAs including known microRNAs that are differentially expressed in FSHD2 muscle cells compared to control. Although fewer small RNAs were differentially expressed during muscle differentiation in FSHD2 cells compared to controls, most of the known myogenic microRNAs, such as miR1, miR133a and miR206 were induced in both FSHD2 and control muscle cells during differentiation. Our small RNA sequencing data analysis also revealed both DUX4- and SMCHD1-specific changes in FSHD2 muscle cells. Six FSHD2 microRNAs were affected by DUX4 overexpression in control myoblasts, whereas increased expression of tRNAs and 5S rRNAs in FSHD2 muscle cells was largely recapitulated in SMCHD1-depleted control myoblasts. Altogether, our studies suggest that the small noncoding RNA transcriptome changes in FSHD2 might be different from those in FSHD1 and that these differences may provide new diagnostic and therapeutic tools specific to FSHD2.